LAND COVER CHANGES IN ROMANIA BASED ON CORINE LAND COVER INVENTORY 1990–2012 - JENICĂ HANGANU; ADRIAN CONSTANTINESCU (Revue Roumaine de Géographie)
From 1990 to 2012 the European Environment Agency implemented the CORINE Programme (Co-ordination of Information on the Environment). In Romania, the National Reference Centre implemented the national CORINE Land Cover (CLC) inventory to the reference years 1990, 2000, 2006 and 2012 to derive the CLC update and land cover change data base. The information obtained within the project, as digitized land cover maps on scale 1:100 000 for the whole territory of Romania represent a reference data set for spatial and territorial analysis at different territorial levels. Land cover statistics and spatial distribution of classes and trend of changes along the 1990–2012 period are presented.